Hubungan Indeks Massa Tubuh (IMT), Kadar Hemoglobin dan Paparan Asap Rokok dengan Kejadian Dismenore: Relationship between Body Mass Index (BMI), Hemoglobin Levels and Exposure to Cigarette Smoke with the Incidence of Dysmenorrhea - Arisani, Greiny (Jurnal Kebidanan Midwiferia, 2019)
Reproductive health is an important problem for adolescents. The earliest change in adolescents is to start menstruating which can cause dysmenorrhea. Dysmenorrhea affects learning activities and indirectly affects the quality of life of adolescents. There are several risk factors that are considered to have a relationship with dysmenorrhea including body mass index (BMI), hemoglobin levels and exposure to cigarette smoke. This study aims to determine the relationship of body mass index (BMI), hemoglobin levels and exposure to cigarette smoke with the occurrence of dysmenorrhea. This study was an observational analytic study with astudy design Cross Sectional. The sample in this study were female students of the Midwifery Department of Health at the Palangka Raya Ministry of Health. The research instruments were in the form of questionnaires s. Data analysis was done by Chi Square and Logistic Regression. The statistical test results showed a significant relationship between Body Mass Index (BMI), Hemoglobin Levels and Cigarette Smoke Exposure with Occurrence of Dysmenorrhea (p <0.05). The results of the logistic regression analysis obtained a determination coefficient value of 0.461 so that it can be concluded that the variable body mass index (BMI), hemoglobin level and exposure to cigarette smoke had a contribution of 46.1% to the incidence of dysmenorrhea and 53.9% influenced by other factors. Body Mass Index (BMI) OR = 14,920, Hemoglobin Level (Hb <12 gram / dl) OR = 5,897 and cigarette smoke exposure OR = 3,289 is a risk factor for dysmenorrhea in adolescents.